2016
DOI: 10.1002/qj.2924
|View full text |Cite
|
Sign up to set email alerts
|

Near‐surface strong winds in a marine extratropical cyclone: acceleration of the winds and the importance of surface fluxes

Abstract: A rapidly developing extratropical cyclone named Tini brought strong winds to Ireland and the United Kingdom on 12 February 2014. A mesoscale-model simulation is used to analyze the development of the strong winds through the terms in the horizontal momentum equation. The maximum of near-surface wind speed equatorward of the cyclone was composed of two different airstreams that underwent different paths to acceleration. First, horizontally moving air in the cold conveyor belt was accelerated by the along-flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 49 publications
7
48
0
Order By: Relevance
“…In other research (Browning et al , ) a similar role for evaporative cooling in destabilizing the boundary layer was identified in a rapidly deepening cyclone at the stage of frontal fracture. Destabilization of the boundary layer can be due to the evaporative cooling mechanism as in these studies or to surface fluxes if the underlying surface is warm enough (Slater et al , ). Further research is required to establish the relative importance of these mechanisms but, one way or another, a destabilized boundary layer is an important ingredient of situations when extratropical storms produce damaging surface winds.…”
Section: Discussionmentioning
confidence: 99%
“…In other research (Browning et al , ) a similar role for evaporative cooling in destabilizing the boundary layer was identified in a rapidly deepening cyclone at the stage of frontal fracture. Destabilization of the boundary layer can be due to the evaporative cooling mechanism as in these studies or to surface fluxes if the underlying surface is warm enough (Slater et al , ). Further research is required to establish the relative importance of these mechanisms but, one way or another, a destabilized boundary layer is an important ingredient of situations when extratropical storms produce damaging surface winds.…”
Section: Discussionmentioning
confidence: 99%
“…As recognised by Browning (), gradient wind balance is sufficient to account for a large part of the strength of the winds in the frontal‐fracture region. Subsequent studies (Schultz and Sienkiewicz, ; Coronel et al ; Slater et al ) have demonstrated association between SJ‐type airstreams and frontolysis, divergent Q vectors, and/or quasi‐geostrophic omega. This body of work has established that downwards advection of strong winds by the frontolytical secondary circulation (implicitly found in the frontal‐fracture region of a cyclone) followed by acceleration by the low‐level pressure gradient can give rise to strong winds.…”
Section: Introductionmentioning
confidence: 99%
“…The last subsection contains a comparison with a coarser model simulation; this comparison is included to reconcile our results, which show a clear contribution of mesoscale instability release to the generation and descent of the SJ in windstorm Tini , with the results of other studies that have concluded that this mechanism does not contribute. In particular, Slater et al () also show results from a simulation of windstorm Tini , but attribute the SJ‐like feature to large‐scale dynamics. Since their simulation used a resolution that is too coarse to resolve mesoscale instability release, this part of our study addresses the role that model resolution has on the diagnosed contributions of mechanisms to SJs.…”
Section: Introductionmentioning
confidence: 99%
“…Browning and Field, ), but definitive evidence of the existence of the sting jet requires trajectories and/or other diagnostics (e.g. Smart and Browning, ; Slater et al ., ; ).…”
Section: Discussionmentioning
confidence: 99%
“…Clark et al ., ; Gray et al ., ; Martínez‐Alvarado et al ., 2014b; Browning et al ., ), but others have described cases in which the importance of moist processes was questionable (e.g. Schultz and Sienkiewicz, ; Baker, ; Baker et al ., ; Smart and Browning, ; Slater et al ., ; ; Coronel et al ., ).…”
Section: The Wind Maximum Has More Than One Sourcementioning
confidence: 99%